Interpretation of space-time temperature variations in Antarctica in connection with changes in the geomagnetic field and low stratospheric ozone - Bakhmutov, V.; Kilifarska, N.; Melnyk, G.; Shenderovs’ka, O. (Ukrainian Antarctic Journal, 2020)
In this work we review space-time temperature variations in Antarctica and possible ways the various geophysical factors caused by fluctuations of the main geomagnetic field could influence it. We analyzed data of direct ground observations of temperature and the geomagnetic field, and data of ERA-20CM and ERA Interim on air temperature variation, ozone concentration and specific humidity at the upper troposphere–lower stratosphere level. The values of module of total intensity of the magnetic field vector were calculated according to the IGRF model. Time series of galactic cosmic rays (annual data since 1700) were provided by the World Data Center for Paleoclimatology. Solar proton fluxes with energies ≥10 MeV were taken from several sources: (1) historical reconstructions of large solar proton events before 1950, (2) published data on solar proton fluxes and (3) satellite data on solar proton events. Time series were analyzed using Statistica and Microsoft Excel software. The fastest decrease in geomagnetic field’s intensity occurs in West Antarctica where there is also seen the largest increase in surface temperature in the region during the XXth century. Besides that, in Central and East Antarctica there are trends towards decreasing of air temperature and strengthening of geomagnetic field. The concomitance might indicate a link between the geomagnetic field and regional climatic change. We explain it thusly: (i) the geomagnetic field controls the charged particles flux entering the Earth’s atmosphere; (ii) the charged particles influence the ozone concentration near tropopause and through this, the temperature and humidity in the upper troposphere–lower stratosphere, (iii) the induced changes in humidity near tropopause have an effect on surface temperature by strengthening or weakening the greenhouse effect. Changes in the geomagnetic field intensity can be one of the factors which shape the temporal and regional variability of surface temperature. Low intensity of the geomagnetic field and the highest speed of its changes in the West Antarctica correspond to the systematically low ozone concentration and increased air humidity near tropopause. The factors cause retention of Earth’s longwave radiation in the troposphere due to the greenhouse effect which results in regional warming in the region.